Neonatal Hypothermia in Low-Resource Settings - Mullany, Luke C. (Seminars in perinatology, 2010)
Hypothermia among newborns is considered an important contributor to neonatal morbidity and mortality in low-resource settings. However, in these settings only limited progress has been made towards understanding the risk of mortality after hypothermia, describing how this relationship is dependent on both the degree or severity of exposure and the gestational age and weight status of the baby, and implementing interventions to mitigate both exposure and the associated risk of poor outcomes. Given the centrality of averting neonatal mortality to achieving global milestones towards reductions in child mortality by 2015, recent years have seen substantial resources and efforts implemented to improve understanding of global epidemiology of neonatal health. In this article, a summary of the burden, consequences, and risk factors of neonatal hypothermia in low-resources settings is presented, with a particular focus on community-based data. Context-appropriate interventions for reducing hypothermia exposure and the role of these interventions in reducing global neonatal mortality burden are explored.